2018
DOI: 10.1111/and.13163
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Indices as a marker for early prediction of erectile dysfunction in diabetic patients

Abstract: Erectile dysfunction is one of the major concerns in diabetic patients. Platelet Indices including mean platelet volume, platelet count and platelet distribution width are important biomarkers for platelet activation and pathophysiology of atherothrombosis. Measurement of Platelet Indices may early predict erectile dysfunction in diabetic men. This study aimed to measure Platelet Indices in diabetic patients with erectile dysfunction and to correlate between them and erectile dysfunction especially of vasculog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
(28 reference statements)
1
16
0
1
Order By: Relevance
“…Studies demonstrated that over 95% of cases could be successfully treated. 7,8 ED is a private issue. Many men feel embarrassed to disclose and discuss the problem with their physician, or even their life-partner.⁹ There were currently lack of study have been done on ED in patients with DM.…”
mentioning
confidence: 99%
“…Studies demonstrated that over 95% of cases could be successfully treated. 7,8 ED is a private issue. Many men feel embarrassed to disclose and discuss the problem with their physician, or even their life-partner.⁹ There were currently lack of study have been done on ED in patients with DM.…”
mentioning
confidence: 99%
“…Of the remaining 20 articles, 6 were excluded with different reasons, which included unable to obtain the related data distribution in cases and controls, data not qualified (controls having ED). Finally, the remaining 14 studies (Akbas et al, ; Aldemir et al, ; Aldemir et al, ; Bayraktar & Albayrak, ; Ciftci et al, ; Ciftci et al, ; El Taieb, Hegazy, Maklad, & Khairy, ; Guo et al, ; Guo et al, ; La Vignera et al, ; Otunctemur et al, ; Sambel et al, ; Senturk et al, ; Wang et al, ) were enrolled in our systematic review and meta‐analysis, all of which were identified as case–control studies. No further articles were identified for inclusion through the repeated cited reference screening.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies reporting the PLT levels in ED (1580 subjects) and non‐ED cases (977 subjects) were included in the meta‐analysis (Akbas et al, ; Aldemir et al, ; Aldemir et al, ; Bayraktar & Albayrak, ; Ciftci et al, ; Ciftci et al, ; El Taieb et al, ; Guo et al, ; Guo et al, ; Otunctemur et al, ; Sambel et al, ; Senturk et al, ; Wang et al, ). The pooled SMD indicated that individuals with ED had about 0.215 k/μl higher of PLT levels than those without ED (SMD [95% CI] = 0.215 [0.133–0.297], p = 0.000), with severe heterogeneity existed ( I 2 = 90.1%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also established an MPV cut-off of 9.65 fl for arterial ED diagnosis, with a specificity of 91.7% [33]. Conversely, a study conducted on 30 diabetic patients with ED did not find any difference between the different vasculogenic ED subtypes, thus suggesting that the increase in MPV in diabetic patients is correlated with vasculogenic ED regardless of the type of dysfunction (arterial, venous, or mixed) [34].…”
Section: Mean Platelet Volume and Erectile Dysfunctionmentioning
confidence: 99%